2011
DOI: 10.1177/0363546511411700
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Major League Baseball Injuries

Abstract: Injuries in MLB resulting in disabled list designation are common. Upper extremity injuries were predominant in pitchers, while lower extremity injuries are more common in position players. These data may be used in the development of a formal MLB injury database, as well as in the development and implementation of specific preseason training and in-season conditioning for injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
271
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(289 citation statements)
references
References 3 publications
8
271
9
1
Order By: Relevance
“…This is likely because of the fact that knee injuries compose only 7.7% of all injuries in Major League Baseball (MLB). 15 The purpose of this study was 3-fold: first, to investigate the rate of return to play for MLB athletes after ACLR; second, to determine the impact of ACL injury on the ability to perform baseball-specific planting and pivoting tasks (batting and stealing bases); and third, to explore the effect of the injured side on these metrics. We hypothesized that performance statistics for cutting and pivoting activities (e.g., batting and stealing bases) would deteriorate after ACLR and that injury to the rear (power-generating) batting leg would result in worse batting performance after ACLR than injury to the lead batting leg.…”
mentioning
confidence: 99%
“…This is likely because of the fact that knee injuries compose only 7.7% of all injuries in Major League Baseball (MLB). 15 The purpose of this study was 3-fold: first, to investigate the rate of return to play for MLB athletes after ACLR; second, to determine the impact of ACL injury on the ability to perform baseball-specific planting and pivoting tasks (batting and stealing bases); and third, to explore the effect of the injured side on these metrics. We hypothesized that performance statistics for cutting and pivoting activities (e.g., batting and stealing bases) would deteriorate after ACLR and that injury to the rear (power-generating) batting leg would result in worse batting performance after ACLR than injury to the lead batting leg.…”
mentioning
confidence: 99%
“…In a 16-year study by the National Collegiate Athletic Association (NCAA) baseball had the lowest practice injury rate and third lowest game injury rate out of 14 sports [ 2 ] . At the professional level the injury rate for Major League Baseball (MLB), 3.6/1 000 exposures [ 10 ] , compares favorably to the National Basketball Association's rate of 21.4/1 000 exposures [ 12 ] . Much of baseball's lower risk is attributable to its classifi cation as a "limited contact sport" [ 11 ] .…”
Section: Injury Risk Due To Collisions In Major League Baseballmentioning
confidence: 99%
“…A 15-day DL requirement meant less severe injuries were not included and while injury rates do decrease over the course of a season [ 10 ] some injuries late in the season could have been missed since the DL may not be utilized as often in September when rosters are expanded. A shorter time loss injury defi nition and capturing additional late season injuries would only strengthen the conclusions regarding injury risk made by this study.…”
mentioning
confidence: 99%
“…[1][2][3] Authors of epidemiologic studies across various sports leagues have indicated that HSI is one of the highest ranked causes of missed playing time in both practice and competition, with an average of 8 to 24 days missed per injury. 1,[4][5][6][7][8][9] Even more alarming is the reinjury rate after return to play (RTP), which ranges from 12% to 34%, 1,10 with the reinjury usually resulting in more severe symptoms and a longer recovery time than the initial injury. 2 Management of hamstrings strains is challenging to the patient and athletic trainer (AT), as the recovery and healing process is slow and symptoms usually persist for some time.…”
mentioning
confidence: 99%